Association between the C-reactive protein to albumin ratio and adverse clinical prognosis in patients with young stroke - Du, Yang; Zhang, Jia; Li, Ning; Guo, Jiahuan; Liu, Xinmin; Bian, Liheng; Zhao, Xingquan; Liu, Yanfang (Frontiers in Neurology, 2022)
Background: Inflammatory response plays an important role in ischemic stroke and the proportion of stroke in young adults has increased rapidly in recent years. C-reactive protein to albumin ratio (CAR) is a new index reflecting the overall inflammatory status of patients with major diseases, while no studies have reported the relationship between CAR and young stroke so far. Methods: The basic characteristics and laboratory examination results of participants including CAR were taken at admission. The modified Rankin Scale (mRS) scores at 30-day follow-up and 90-day follow-up were obtained from all patients. All participants included in the study were classified into four groups according to CAR quartiles (Q1-Q4). Logistic regression was used to analyze the relationship between different CAR levels and adverse outcomes (mRS 3-6 and mRS 2-6). We also plotted receiver operating characteristic (ROC) curves of CAR for adverse clinical outcomes and calculated area under the curve (AUC) values and cutoff values. Results: A total of 630 patients with young stroke were enrolled in our study. In the multivariate logistic regression model, at 30-day follow-up, the Q3 and Q4 (significantly increased CAR) groups showed an elevated risk of mRS score of 2-6 (OR, 2.94; 95% CI, 1.40-6.16, p<0.01 and OR, 4.01; 95% CI, 1.88-8.91, p<0.01). At 90-day follow-up, the Q3 and Q4 groups still showed an elevated risk of mRS score of 2-6 (Q3, OR, 2.76; 95% CI, 1.30-5.86, p<0.01 and Q4, OR, 2.63; 95% CI, 1.22-5.65, p<0.01). Conclusion In this study, we suggested that a significant increased CAR was independently associated with increased risks of adverse outcome in patients with young stroke.